Efeito do manejo convencional e orgânico na qualidade do grão e bebida de café - Goncalves, Jessica de Melo (2022)
The different soil management practices adopted in coffee cultivation systems can influence the chemical attributes of the soil and consequently the mineral nutrition of plants, interfering with the quality of fruits, beans and coffee beverage. The different soil management practices adopted in coffee cultivation systems can influence the chemical attributes of the soil and consequently the mineral nutrition of plants, interfering with the quality of fruits, beans and coffee beverage. The objective of the study was to evaluate the effects of soil chemical attributes and leaf mineral nutrition on the quality of coffee beans and beverage (Catuaí Vermelho, Coffea arabica L.) under conventional and organic systems. Soil chemical attributes, leaf contents, grain and beverage quality were evaluated. The pH and the contents of organic matter, magnesium, boron, copper, iron and manganese in the soil did not differ between the conventional and organic systems. The highest levels of sulfur and phosphorus in the soil were observed in the organic system and the highest levels of zinc and potassium in the conventional system. The foliar contents of nitrogen, phosphorus, magnesium and boron were higher in the coffee plants in the conventional system and the foliar contents of potassium and zinc in the organic system. There was evidence on the behavior of soil samples and leaf tissue from the two systems, which offered favorable conditions for fruit development, presenting in the organic system higher values of TSS and grain diameters and in the quality of the coffee beverage the sensory attributes presented similar scores, both coffees received a score of 83, being classified as specialty coffees.